Pengaruh Iklim Organisasi terhadap Loyalitas Pegawai pada Dinas Perhubungan Kota Jambi - Ferzi, Noviardi; Albetris, Albetris; Wahab, Abdul (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to analyze the influence of organizational climate on employee loyalty at the Jambi City Transportation Agency. This study uses a quantitative approach and data processing in this study uses SPSS software. Involving 95 respondents selected through purposive sampling techniques from a total population of 124 employees. The results of the study with simple linear regression analysis showed that organizational climate has a significant effect on employee loyalty at the Jambi City Transportation Agency with a determination coefficient value of 54.3%, which means that variations in employee loyalty can be explained by organizational climate.